Seroprevalence of in Children from Urban and Rural Areas of Ilam Province, West Iran - Sahar Shokouhi; Jahangir Abdi (Osong Public Health and Research Perspectives, 2018)
Objectives The present study was performed to determine the seroprevalence of Toxocara in children ≤ 10 years old, from rural and urban areas of Ilam. Methods Serum samples from 383 children ≤ 10 years old, were selected randomly from rural and urban areas of Ilam province and surveyed using enzyme-linked immunosorbent assays. Results The total rate of infection with Toxocara was 22% (31% with a history of contact with dogs and cats, and 14% without a history of contact). Of those infected, 23% were male and 18% were female, 36% lived a rural life and 20% had an urban life. A significant correlation was found between the incidence of disease, and urban and rural life, as well as exposure to dogs and cats. There was no correlation between prevalence and gender or age. Conclusion Given the high prevalence of infection with Toxocara amongst children in Ilam province, preventive work in the community such as education in risk management and periodic treatment with anti-parasitic drugs and elimination of stray dogs and cats is an appropriate measure.